The Effectiveness Of Village Fund Disbursement On The Performance Of Oil Palm Farming Village Enterprises In Tumbuk Village, Pagar Jati Sub-District, Central Bengkulu District - Yusdayanti, Nirta Pera; Fariadi, Herri; Nurmalia, Ana (Utami Publisher, 2025)
BUMDes (Village-Owned Enterprises) is an institution that operates in the field of processing village economic resources which aims to improve community businesses which create jobs, develop the economy and increase the village's original income. BUMDes is an institution that operates in the field of managing village economic assets and resources which aims to optimize village assets, improve community businesses, create business opportunities, create jobs, develop the village economy and increase village income. If the management of BUMDes is optimal, then the village will become an independent village and be able to eradicate poverty by improving village welfare. This research aims to find out how effective the distribution of village funds is to the Bumdes, to find out the performance of village funds on the performance of the Bumdes, and to find out the influence of the Effectiveness of Fund Distribution Villages on the Performance of Bumdes for Palm Oil Farming in Tumbuk Village, Pagar Jati District, Central Bengkulu Regency. The method used is a quantitative descriptive method using a Likert scale and simple linear regression analysis. The results of the research show that the effectiveness of village fund distribution on the performance of the oil palm farming BUMDes in Tumbuk Village, Pagar Jati District, Central Bengkulu Regency is 68.8 in the effective category. Meanwhile, the performance of village funds for the oil palm farming BUMDes in Tumbuk village was 69.13 in the high category. The results of statistical tests show that there is an influence on the effectiveness of the distribution of village funds on the performance of the Bumdes for oil palm farming in Tumbuk village.